Feasibility of the automatic ingestion monitor (AIM-2) for infant feeding assessment: a pilot study among breast-feeding mothers from Ghana. Issue 10 (26th October 2022) - Cerminaro, Caroline; Sazonov, Edward; McCrory, Megan A; Steiner-Asiedu, Matilda; Bhaskar, Viprav; Gallo, Sina; Laing, Emma; Jia, Wenyan; Sun, Mingui; Baranowski, Tom; Frost, Gary; Lo, Benny; et al.
Abstract: Objective: Passive, wearable sensors can be used to obtain objective information in infant feeding, but their use has not been tested. Our objective was to compare assessment of infant feeding (frequency, duration and cues) by self-report and that of the Automatic Ingestion Monitor-2 (AIM-2). Design: A cross-sectional pilot study was conducted in Ghana. Mothers wore the AIM-2 on eyeglasses for 1 d during waking hours to assess infant feeding using images automatically captured by the device every 15 s. Feasibility was assessed using compliance with wearing the device. Infant feeding practices collected by the AIM-2 images were annotated by a trained evaluator and compared with maternal self-report via interviewer-administered questionnaire. Setting: Rural and urban communities in Ghana. Participants: Participants were thirty eight (eighteen rural and twenty urban) breast-feeding mothers of infants (child age ≤7 months). Results: Twenty-five mothers reported exclusive breast-feeding, which was common among those < 30 years of age ( n 15, 60 %) and those residing in urban communities ( n 14, 70 %). Compliance with wearing the AIM-2 was high (83 % of wake-time), suggesting low user burden. Maternal report differed from the AIM-2 data, such that mothers reported higher mean breast-feeding frequency (eleven v . eight times, P = 0·041) and duration (18·5 v . 10 min, P = 0·007) during waking hours. Conclusion: The AIM-2 was a feasible tool for the assessment of infant feeding among mothers in Ghana as a passive, objective method and identified overestimation of self-reported breast-feeding frequency and duration. Future studies using the AIM-2 are warranted to determine validity on a larger scale.